Epistasis in Modifying Genes: Key Factor to Differentiate Clinical Subtypes in Neurodevelopmental Disorders - José Ignacio Lao Villadóniga (Revista Finlay)
Neurodevelopmental disorders group conditions in which the growth and development of the brain is altered. This can damage both the neurocognitive and behavioral spheres such as the development of language, emotions, behavior, self-control, learning and memory, and also motor functions. They include attention deficit and hyperactivity disorders, autism spectrum disorders, communication problems, intellectual development problems, as well as various specific learning disorders and various motor disorders. They begin early in a child's development and can continue throughout life. In each one, a wide heterogeneity is observed in terms of manifestations, evolution and their response to support interventions and treatments. In this article, we consider the impact that the interaction of genetic polymorphisms in several genes, known as epistasis, can have within the main etiopathogenic pathways to be taken into account in these cases and how these interactions affect each “facilitating” genotype. It interacts with the rest of the factors, such as non-genetic ones.